PEMBUATAN POSTER EDUKASI PENGENALAN NAMA SAYURAN DALAM 3 BAHASA (KAMBERA, INDONESIA, DAN INGGRIS) UNTUK SEKOLAH DASAR DI KOTA WAINGAPU - Raynesta Mikaela Indri Malo; Suryani Kurniawi K. L. Kapoe; Itha Priyastiti; Niken M. P. A. Galla; Helena Magdalena; Eduard Yanto Bulu; Katarina Katanna; Krisna Rambu Gagah; Alvalen Febrika Jekson (Jurnal Abdi Insani, 2022)
Although the government has accommodated English to be included in the realm of local content, a number of obstacles including the limited number of teachers and funds have resulted in the implementation of the introduction of English being not optimal. Similar problems occur in the Kambera language which has not yet become a part of education in East Sumba, especially in urban areas. Seeing the importance of using English and local languages ​​in schools both as the language of instruction and as part of subjects, the solution that must be taken is to include elements of regional languages ​​in learning in elementary schools. This Community Service activity aims to introduce English and Kambera, as the local languages ​​of East Sumba, to elementary school students in Waingapu through the names of vegetables presented through posters. The method of implementing this activity begins with qualitative data collection and analysis. There are 50 kinds of vegetables which are divided into 3 major groups of vegetables, namely root and tuber vegetables, seed and fruit vegetables, and leaf and stem vegetables, which are then presented in 5 posters. The results of this activity indicate that not all students in every school have good English skills because it has not been implemented in the curriculum, then students do not have knowledge of the Kambera language which is a local language in East Sumba due to lack of early introduction. The conclusion that can be drawn is that the introduction and improvement of English and Kambera language skills in the community needs to be carried out on an ongoing basis. The poster media used in this activity can also support the sustainability of this activity because it can still be used as a learning medium in other schools.